2011
DOI: 10.4236/ns.2011.32014
|View full text |Cite
|
Sign up to set email alerts
|

Study of anisotropic variation of cosmic rays intensity with solar activity

Abstract: The annual average values of amplitudes and phases of first two harmonics of cosmic ray anisotropy have been derived by using the harmonic analysis technique for the period 1989 to 2004, which covers mostly the major period of solar cycles 22 and 23. In this paper we have taken the pressure corrected hourly data for Kiel neutron monitor station (cut off rigidity ≈ 2.29 GV) to derive the harmonic component of cosmic ray daily variation and compared with the data of Halekala neutron monitor (cut off rigidity ≈ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The correlation of solar-terrestrial and galactic-terrestrial leads to structural cloud formation in the Earth's atmosphere (Todd and Kniveton (2001); Sun and Bradley (2002); de Wit and Watermann (2010); Yurchyshyn and Tripathi (2010); Tiwari et al (2011); Mörner (2013)). Several other authors have also suggested that the SW & CR plays an important role in rain-yielding cloud formation, irrespective of geographical location (Ney (1959); Svensmark (1998); Pallé Bagó and Butler (2000); Marsh and Svensmark (2000); Carslaw et al (2002); Pallé and Butler (2002); Marsh and Svensmark (2003); Tinsley and Yu (2003); Usoskin and Kovaltsov (2008)), but a discussion on the importance of the interaction period of ∼ 4.66-year (which happens to be QBO period) between SW and CR with rainfall was awaited.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of solar-terrestrial and galactic-terrestrial leads to structural cloud formation in the Earth's atmosphere (Todd and Kniveton (2001); Sun and Bradley (2002); de Wit and Watermann (2010); Yurchyshyn and Tripathi (2010); Tiwari et al (2011); Mörner (2013)). Several other authors have also suggested that the SW & CR plays an important role in rain-yielding cloud formation, irrespective of geographical location (Ney (1959); Svensmark (1998); Pallé Bagó and Butler (2000); Marsh and Svensmark (2000); Carslaw et al (2002); Pallé and Butler (2002); Marsh and Svensmark (2003); Tinsley and Yu (2003); Usoskin and Kovaltsov (2008)), but a discussion on the importance of the interaction period of ∼ 4.66-year (which happens to be QBO period) between SW and CR with rainfall was awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Network and shows how the nodes associated with interconnection network are connect and communicate and represent in different lemma possible [6,8].…”
Section: Tiwari Et Al Gives An Excellent Survey Of Interconnectionmentioning
confidence: 99%
“…The last few decades have witnessed an upsurge of parallel computing and Artificial Intelligence [7,8]. Unprecedented growth in the research work being published in the related field.…”
Section: Vector Analysismentioning
confidence: 99%